2018
DOI: 10.26444/aaem/82539
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with interpersonal relations among employees of State Forests in Poland

Abstract: Introduction and objective. The aim of this study is to assess the interpersonal relations of employees of State Forests in Poland, as well as to indicate the factors related to the level of satisfaction with the relations among people employed in similar positions, and relations with superiors. Materials and method. The issues investigated were developed based on research conducted between 2014-2015 among employees of State Forests in Poland. In each of the 9 forest districts selected, 25 people were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…However, on the contrary, Toker (2011), Lachowski et al (2018), andLiu et al (2021) found that gender has no significant effect on job satisfaction. When we consider the extant literature on job satisfaction in the banking sector, the significance of gender in determining job satisfaction is yet to be studied.…”
Section: Gender and Job Satisfactionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, on the contrary, Toker (2011), Lachowski et al (2018), andLiu et al (2021) found that gender has no significant effect on job satisfaction. When we consider the extant literature on job satisfaction in the banking sector, the significance of gender in determining job satisfaction is yet to be studied.…”
Section: Gender and Job Satisfactionmentioning
confidence: 98%
“…Extant studies evidence that age positively affects job satisfaction (Karsh et al, 2005;Buker & Dolu, 2010;Chou et al, 2011;Lachowski et al, 2018). Employees in the oldest group show the highest job satisfaction, while young employees have minor satisfaction (Rogozinska-Pawelczyk, 2018;DeVaney & Chen, 2003).…”
Section: Age and Job Satisfactionmentioning
confidence: 99%
“…In the United States of America, Lim & Cortina (2005) highlight that workplace poor interpersonal relations have to be managed to avoid impaired employee performance. In Poland, Lackowski et al (2018) are of the view that low level of relations of among teachers do contribute to low performance and job satisfaction.…”
Section: The Effects Of Poor Teacher-teacher Professional Relationsmentioning
confidence: 99%
“…Satisfaction from work can be regarded as an indicator of wellness, especially mental and social in the workplace, but also as a factor influencing other spheres of human life (somatic health, family situation) (Lachowski et. al 2018).…”
Section: Key Concepts Job Satisfactionmentioning
confidence: 99%